Persistent Cognitive Dysfunction Following Systemic Chemotherapy in Women with Breast Cancer - Mazur, Weronika; Pawelec, Natalia; Hańczyk, Edyta; Piecuch, Dawid; Kopciał, Szymon; Kornatowska, Karolina; Drużdżel, Anna (Quality in Sport, 2026)
Chemotherapy-related cognitive impairment (CRCI), commonly known as “chemobrain,” is a prevalent and clinically significant complication in breast cancer survivors. Cognitive deficits primarily affect memory, attention, executive function, processing speed, and verbal fluency, and may persist for months to years after treatment. CRCI arises from multiple mechanisms, including direct neurotoxicity, neuroinflammation, oxidative stress, mitochondrial dysfunction, hormonal alterations, genetic susceptibility, psychosocial stressors, and gut–brain axis changes. Neuroimaging studies demonstrate structural and functional brain alterations such as gray matter reduction, white matter microstructural changes, disrupted connectivity, and compensatory cortical hyperactivation, particularly within frontoparietal and temporal networks. Subjective cognitive complaints often correspond with objective deficits, although considerable heterogeneity exists. Precision approaches, including machine learning-based neuroimaging biotyping and multimodal cognitive assessment, enable identification of biologically distinct subgroups and improve risk stratification. Non-pharmacological interventions such as cognitive rehabilitation, physical activity, mindfulness, and psychosocial support have shown efficacy, whereas pharmacological options remain limited. Integrating biological, neuroimaging, genetic, and psychosocial data is essential for developing individualized strategies to preserve cognitive function and quality of life. Future research should prioritize longitudinal studies, biomarker discovery, ecological cognitive monitoring, and digital therapeutics to optimize precision survivorship care.